Site-Selective Switching Strategies to Functionalize Polyazines - Dolewski, Ryan D. (J Am Chem Soc, 2018)
Many drug fragments and therapeutic compounds contain multiple pyridines and diazines. Developing site-selective reactions where specific C–H bonds can be transformed in polyazine structures would enable rapid access to valuable derivatives. We present a study that addresses this challenge by selectively installing a phosphonium ion as a versatile functional handle. Inherent factors that control site-selectivity are described along with mechanistically driven approaches for site-selective switching, where the C–(+)PPh(3) group can be predictably installed at other positions in the polyazine system. Simple protocols, readily available reagents and application to complex drug-like molecules make this approach appealing to medicinal chemists.